2017
DOI: 10.11152/mu-892
|View full text |Cite
|
Sign up to set email alerts
|

The role of echocardiography in fetal tachyarrhythmia diagnosis. A burden for the pediatric cardiologist and a review of the literature.

Abstract: Supraventricular tachyarrhythmia represents the most frequent fetal dysrhythmia. In the lack of diagnosis and treatment these fetuses may develop hydrops and even death. For the therapeutic approach it is important to establish the diagnosis of the type of supraventricular tachycardia. In this paper we report 29 cases with different types of supraventricular tachycardia in which the diagnosis was established using our own protocol, which allowed us to make the difference between the types of tachycardia (atrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Fetal malformations present multidisciplinary involvements regarding the diagnosis, the therapeutic approach and the prognosis [18][19][20][21][22][23][24][25][26][27][28]. Therefore, prenatal diagnosis is the cornerstone factor that can influence the prognosis of these fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal malformations present multidisciplinary involvements regarding the diagnosis, the therapeutic approach and the prognosis [18][19][20][21][22][23][24][25][26][27][28]. Therefore, prenatal diagnosis is the cornerstone factor that can influence the prognosis of these fetuses.…”
Section: Discussionmentioning
confidence: 99%
“… 16 More critically, there is an insufficient number of pediatric cardiologists or congenital cardiac sonographers who are experienced in performing a comprehensive cardiac ultrasound. 17 Pulse oximetry has been recommended as a reliable screening tool of CHD for newborns in a number of developed countries. 18 21 Nevertheless, several recent pioneering studies have obtained an extremely high specificity, but only a moderate sensitivity, of pulse oximetry in detecting CHD.…”
Section: Introductionmentioning
confidence: 99%
“…In a non-randomized prospective study on 100 fetuses at 15-40 weeks of gestation for cardiac referal, 45 fetuses had cardiac arrhythmias, including premature atrial contractions (PACs) (28/45, 62.2%), atrial bigeminal ectopic beats (3/45, 6.7%), premature ventricular contractions (PVCs) (2, 4.4%), supraventricular tachycardia (SVT) (5/45, 11.1%), ventricular tachycardia (1, 2.2%), second-degree atrioventricular (AV) block (1, 2.2%) and complete AV block (5/45, 11.1%) [3]. A 10-year observational study on the pregnant women demonstrated 29 cases of fetal arrhythmias: 12 (41.4%) of which were fetal tachycardias (10 cases with SVT, 2 cases with atrial flutter (AF)), 5 (17.2%) were fetal bradyarrhythmias (all 5 cases with AV block), and 12 (41.4%) were fetal irregular cardiac rhythms (premature atrial beats) [4]. The overall incidence of malignant fetal arrhythmias, such as complete AV block and SVT, are relatively rare, found in 1:5000 pregnancies [5].…”
Section: Introductionmentioning
confidence: 99%